1982
DOI: 10.1680/geot.1982.32.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Response characteristics of cylindrical piezometers

Abstract: The finite difference solutions presented for the fundamental process of pore pressure equalization in a soil piezometer system are the first of their kind to be published for cyhndrical piezometers. The response-time relationships established for cylindrical piezometers (of radius a and length b) are of the same general form as those for spherical piezomelers, the exact shape of a particular relationship being a function of the ratio a/b, the soil compressibility m and the flexibility of the piezometer measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Comparing the hydraulic conductivity values calculated using both theories shows that the mean value of k* (the hydraulic conductivity calculated using the response time charts derived numerically by Brand and Premchitt (1982)) was much lower than k 90 . Baird and Gaffney (1994) reported that both rigid and compressible soil theories gave values of hydraulic conductivity for each piezometer installation at their fenland site within a factor or two of each other.…”
Section: Comparison Of Rigid and Compressible Techniquesmentioning
confidence: 92%
See 4 more Smart Citations
“…Comparing the hydraulic conductivity values calculated using both theories shows that the mean value of k* (the hydraulic conductivity calculated using the response time charts derived numerically by Brand and Premchitt (1982)) was much lower than k 90 . Baird and Gaffney (1994) reported that both rigid and compressible soil theories gave values of hydraulic conductivity for each piezometer installation at their fenland site within a factor or two of each other.…”
Section: Comparison Of Rigid and Compressible Techniquesmentioning
confidence: 92%
“…Full treatment of the calculations and derivations used are provided by Brand and Premchitt (1982) and Baird and Gaffney (1994) and so only a summary is provided below. Hvorslev's (1951) used the basic differential equation that describes saturated flow through a falling head permeameter to produce a solution to the pore pressure equalisation process between a piezometer system and an incompressible soil.…”
Section: Calculationsmentioning
confidence: 99%
See 3 more Smart Citations